Peligrosidad por inundaciones en una cuenca no aforada: el río Sosa en Monzón (Huesca) y el evento de agosto de 2006 - Domenech Zueco, Sergio; Espejo Gil, Francisco; Ollero Ojeda, Alfredo; Sánchez Fabre, Miguel (Geographicalia, 2014)
The town centre of Monzón has a high risk of flooding caused by the Sosa River which has a typical torrential behaviour. The most recent flood event defined as extraordinary happened in 2006 and this flood was chosen for the modellization of the hydrological response of the basin to a heavy rain event using Geographic Information Systems (GIS). After this episode, hydrological models were fed with real data of rain and the instant maximum discharge that could be registered in the town centre was calculated by means of the geomorphological method, with an estimated peak of 236 m3/s. After the flood, several maps of hazard showing flooding areas according to different flood return periods were published. Hydraulic models show a high risk and, furthermore, they show that the Sosa River can overflow its present banks along the urban reach if the flood has a return period of ten or more years.